FEATURES OF PROOF IN CRIMINAL PROCEEDINGS CONCERNING WAR CRIMES (Bulletin of criminological association of Ukraine, 2024)
The article highlights the peculiarities of evidence gathering in criminal proceedings related to war crimes and identifies the factors that influence the process of proving in such cases. These factors include: the multifaceted nature of war crime elements, which is conditioned by the various forms of criminal acts; the establishment of a contextual element; investigative situations determined by the location of the crime and the ability of pre-trial investigation bodies to access it; the use of innovative technologies and artificial intelligence algorithms; and the state of interaction between pre-trial investigation bodies, the prosecutor’s office, representatives of non-governmental organizations, and journalists.
Keywords: criminal proceedings; war crimes; evidence; evidence-gathering process; contextual element; interaction of pre-trial investigation bodies